Perceived Stigma towards Mental Illness among College Students of Western Nepal - Pokharel, Bandana; Pokharel, Anupama (Birat Journal of Health Sciences, 2018)
Introduction: Stigma of people towards mental illness is still prevailing in our country due to lack of awareness. General public's view about mental illness remains largely unfavourable. The topic of mental illness itself evokes a feeling of fear, embarrassment or even disgust fostering negative attitudes towards mental illness and mentally ill people. There is paucity of articles on this topic from our country. Objective: To investigate college students' stigma towards mental illness and factors associated with the stigma. Methodology: This prospective study was done in College students studying Bachelors of Science. A randomly selected sample of students were explained and asked to fill two forms: First containing socio-demographic data and Second Discrimination Devaluation scale (D-D scale). Data collected were analyzed with SPSS software. Descriptive analysis and Chi-square tests were done. P value less than 0.05 was considered significant. Results: There were 78 students included in the study among which 43.6% (n = 34) had high level of stigma towards mental health. This stigma was not significantly associated with age, gender, year of study among the graduating students, rural or urban background, history of mental illness, or knowing someone with mental illness. Conclusion: Stigma towards mental illness is common even in the educated group of people in the country. With the same level of education, stigma to mental health is not significantly associated with other demographic variables. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 292 - 295